2023
DOI: 10.1029/2022gl101544
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Tilt Effect on Externally Driven Electromagnetic Ion Cyclotron (EMIC) Waves

Abstract: We examine coupling of fluctuations in the solar wind with electromagnetic ion cyclotron (EMIC) waves in the magnetosphere using an advanced full‐wave simulation code, Petra‐M. Dipole tilt dramatically affects the coupling process. While very little wave power can reach the inner magnetosphere without tilt effects, a tilted dipole field dramatically increases the efficiency of the coupling process. Solar wind fluctuations incident at high magnetic latitude effectively reaches the ground along the field line an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Noh et al (2022) reported that ∼54% of the waves observed in the geosynchronous orbit show coincident wave events on the ground at a magnetically connected ground station. On the other hand, E.-H. Kim and Johnson (2023) recently reported that EMIC waves started from high latitudes can easily propagate down to the ground since the efficiency of mode conversion during the propagation dramatically increases. Thus, without a conjugate observation at high latitude in the path of waves, the propagation effect cannot be confirmed.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Noh et al (2022) reported that ∼54% of the waves observed in the geosynchronous orbit show coincident wave events on the ground at a magnetically connected ground station. On the other hand, E.-H. Kim and Johnson (2023) recently reported that EMIC waves started from high latitudes can easily propagate down to the ground since the efficiency of mode conversion during the propagation dramatically increases. Thus, without a conjugate observation at high latitude in the path of waves, the propagation effect cannot be confirmed.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…On the other hand, E.‐H. Kim and Johnson (2023) recently reported that EMIC waves started from high latitudes can easily propagate down to the ground since the efficiency of mode conversion during the propagation dramatically increases. Thus, without a conjugate observation at high latitude in the path of waves, the propagation effect cannot be confirmed.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Moreover, the wave frequencies of PLE at the fundamental frequency or low harmonics are usually below the local H + and He + gyro‐frequencies during their propagation from the low ionosphere to the inner magnetosphere and the effects of multiple ion species contribute significantly to the wave dynamics of PLE in this frequency range. As the wave frequency becomes close to the local characteristic frequencies (e.g., Chen, Jordanova, et al., 2014), the incoming wave may change its wave mode or reversal its polarization passing through the crossover frequency surfaces (e.g., Kim & Johnson, 2016; Pakhotin et al., 2022; Wang, 1971; Xu et al., 2023) or get reflected near the left‐handedly polarized (LHP) wave mode cut‐off frequency or the bi‐ion hybrid resonance frequency surfaces (e.g., Hanzelka et al., 2023; Kim & Johnson, 2023; Smith & Brice, 1964; Vavilov & Shklyar, 2014). Power line networks on the ground can extend from high to low magnetic latitudes (e.g., Dudkin et al., 2015; Wu et al., 2017).…”
Section: Introductionmentioning
confidence: 99%